Production of accurate skeletal models of domestic animals using three‐dimensional scanning and printing technology. Issue 1 (15th September 2017) - Li, Fangzheng; Liu, Chunying; Song, Xuexiong; Huan, Yanjun; Gao, Shansong; Jiang, Zhongling
Abstract : Access to adequate anatomical specimens can be an important aspect in learning the anatomy of domestic animals. In this study, the authors utilized a structured light scanner and fused deposition modeling (FDM) printer to produce highly accurate animal skeletal models. First, various components of the bovine skeleton, including the femur, the fifth rib, and the sixth cervical (C6) vertebra were used to produce digital models. These were then used to produce 1:1 scale physical models with the FDM printer. The anatomical features of the digital models and three‐dimensional (3D) printed models were then compared with those of the original skeletal specimens. The results of this study demonstrated that both digital and physical scale models of animal skeletal components could be rapidly produced using 3D printing technology. In terms of accuracy between models and original specimens, the standard deviations of the femur and the fifth rib measurements were 0.0351 and 0.0572, respectively. All of the features except the nutrient foramina on the original bone specimens could be identified in the digital and 3D printed models. Moreover, the 3D printed models could serve as a viable alternative to original bone specimens when used in anatomy education, as determined from student surveys. This study demonstrated an important example of reproducing bone models to be used in anatomy education and veterinary clinical training. Anat Sci Educ 11: 73–80. © 2017 American Association of Anatomists.